2007
DOI: 10.1158/1535-7163.mct-07-0104
|View full text |Cite
|
Sign up to set email alerts
|

p21 and p27 induction by silibinin is essential for its cell cycle arrest effect in prostate carcinoma cells

Abstract: Recent studies have shown that silibinin induces p21/Cip1 and p27/Kip1 and G 1 arrest in different prostate cancer cells irrespective of p53 status; however, biological significance and mechanism of such induction have not been studied. Here, using two different prostate cancer cell lines DU145 and 22Rv1, representing androgen-independent and androgen-dependent stages of malignancy, first we investigated the importance of p21 and p27 induction in silibininmediated G 1 arrest. Silencing p21 and p27 individually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 42 publications
3
98
0
Order By: Relevance
“…3D). In cancer cells, p21 binds and inactivates cyclin/Cdk complexes primarily mediating a G 1 arrest, 32 but recent studies have also suggested a role in inducing G 2 arrest, either by interfering with the phosphorylation at Tyr 161 of Cdc2-cyclin B1 complex or by limiting the supply of cyclin B1 by causing its proteasomal degradation. 33,34 Since p21 increase correlated with a decrease in cyclin B1 levels by combination treatments (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D). In cancer cells, p21 binds and inactivates cyclin/Cdk complexes primarily mediating a G 1 arrest, 32 but recent studies have also suggested a role in inducing G 2 arrest, either by interfering with the phosphorylation at Tyr 161 of Cdc2-cyclin B1 complex or by limiting the supply of cyclin B1 by causing its proteasomal degradation. 33,34 Since p21 increase correlated with a decrease in cyclin B1 levels by combination treatments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…38 For p21 mRNA level, RNA was isolated by Trizol R method, and specific primers for p21 and β-actin were used for amplification by RT-PCR. 32,43 Tumor xenograft study. Six week old athymic (nu/nu) male nude mice, (NCI-Frederick) were subcutaneously injected with ~three million exponentially growing H1299 cells mixed with equal volume (1:1) of matrigel (BD Biosciences) on the right flank of each mouse.…”
Section: Supplemental Materialsmentioning
confidence: 99%
“…24 Polyphenolic flavonoid silibinin induces G1 arrest by decreasing CDK and cyclin D1 and inducing p21 and p27 which is essential for its anti-proliferative action in PCa. 40,41 Similarly, the indole melatonin reduces cell proliferation by increasing p21 and p53. 24 To some extent, both antioxidants seem to work similarly; they share p21 induction and prevention of NFjB activation induced by TNF, sensitizing PCa cell to apoptosis induced by this cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] It has been shown to modulate the expression of large numbers of miRNAs, small [22][23][24][25] nucleotides long non-coding RNAs, in cancer cells that lead to reduction of tumor growth. [26][27][28] Also, miRNAs play an important role in the modulation of chemosensitivity of tumor cells.…”
Section: Discussionmentioning
confidence: 99%